Rural Areas Facing the Challenge of Economic Diversification: Threats and Opportunities - Francisco Javier Castellano-Álvarez; Rafael Robina-Ramírez; Francisco José Ferreira Silva (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
In the 1990s, the European Commission, through the then-novel Leader Initiative, launched rural development programs whose main objective was economic diversification based on the development of new recreational, touristic, or agro-industrial uses that were emerging. The modest size of the investments associated with these programs and their participatory development models often ensured that these projects were implemented harmoniously in economic, social, and environmental terms. However, there is now a growing interest in other types of investment in rural areas, such as renewable energies, diffuse industrialization projects, and even the extraction and processing of strategic minerals. These investments can be valuable alternatives for achieving the longed-for economic diversification, although it is no less true that they involve abruptly altering the rural environment's traditional agricultural and livestock uses. This Special Issue provided scientific and academic evidence regarding the implementation of these two types of projects: their long-term viability, their impact on the demographic and economic structures of the regions or districts in which they are implemented, and the change in traditional land uses, as well as any other indicators related to the socio-economic development of these environments. This endeavor also included some case studies, which, based on different methodological approaches, approach the subject under study in developed countries and developing regions of the world affected by the same problems.
Keywords: 330; rural revitalization; evolution model; sustainable development; influencing factors; management policy; digital inclusive finance; digital village; technological innovation; digital facilities; digital literacy; fascination; destination; place attachment; pro-environmental behavior; reasonable person model (RPM); integrated development; farmers' income growth; PSM-DID; masking effect; rural tourism; educational homesteads; participation; local action group; multidimensional relative poverty; poverty trap; behavior motivation; agritourism; dehesa; value chain; rural environments; depopulation; Extremadura (Spain); Leader approach; private promoters; semi-structured interviews; SMEs; crafts and services; agricultural valorization; operational; failed and transferred projects; clean toilets; mental health; toilet revolution; IV-Tobit model; China rural; rural families; poverty; catastrophic health expenditures; financial assets; financial literacy; rural areas; development; territorial cohesion; Delphi method; Spain; n/a